Dermatan-4-O-Sulfotransferase-1 Contributes to the Undifferentiated State of Mouse Embryonic Stem Cells - Ogura, Chika; Nishihara, Shoko (Frontiers in Cell and Developmental Biology, 2021)
Mouse embryonic stem cells (mESCs) have the properties of self-renewal and pluripotency. Various signals and growth factors maintain their undifferentiated state and also regulate their differentiation. Glycosaminoglycans are present on the cell surface and in the cell matrix as proteoglycans. Previously, we and other groups reported that the glycosaminoglycan heparan sulfate contributes to both maintenance of undifferentiated state and regulation of mESC differentiation. It has been shown that chondroitin sulfate is needed for pluripotency and differentiation of mESCs, while keratan sulfate is a known marker of human ESCs or induced pluripotent stem cells. We also found that DS promotes neuronal differentiation from mESCs and human neural stem cells; however, the function of DS in the maintenance of mESCs has not yet been revealed. Here, we investigated the role of DS in mESCs by knockdown (KD) or overexpression (O/E) of the dermatan-4-O-sulfotransferase-1 (D4ST1) gene. We found that the activity of the ESC self-renewal marker alkaline phosphatase was reduced in D4ST1 KD mESCs, but, in contrast, increased in D4ST1 O/E mESCs. D4ST1 KD promoted endodermal differentiation, as indicated by an increase in Cdx2 expression. Conversely, Cdx2 expression was decreased by D4ST1 O/E. Wnt signaling, which is also involved in endodermal differentiation, was activated by D4ST1 KD and suppressed by D4ST1 O/E. Collectively, these results demonstrate that D4ST1 contributes to the undifferentiated state of mESCs. Our findings provide new insights into the function of DS in mESCs.